I'm fast! - McMullan, Kate.; McMullan, James, 1934- (New York : Balzer + Bray, 2012)
A train and a car race each other on the way to Chicago.
Ages 4-8.
Keywords: Competition -- Juvenile fiction; Railroad trains -- Juvenile fiction; Automobiles -- Juvenile fiction; Racing -- Juvenile fiction; Railroad stories; Racing -- Fiction; Picture books; Picture books for children; picture books; Picture books; Fiction; Juvenile works; Livres d'images.; Fiction